Magnetic interactions in cubic-, hexagonal- and trigonal-barium iron oxide fluoride, BaFeO2F. (29th June 2016) - Clemens, Oliver; Marco, José F; Thomas, Michael F; Forder, Susan D; Zhang, Hongbin; Cartenet, Simon; Monze, Anais; Bingham, Paul A; Slater, Peter R; Berry, Frank J
Abstract: 57 Fe Mössbauer spectra have been recorded from the hexagonal (6H)- and trigonal (15R)- modifications of BaFeO2 F and are compared with those previously recorded from the cubic form of BaFeO2 F. The spectra, recorded over a temperature range from 15 to 650 K show that all of the iron in all the compounds is in the Fe 3+ state. Spectra from the 6H- and 15R-modifications were successfully fitted with components that were related to the Fe(1) and Fe(2) structural sites in the 6H variant and to the Fe(1), Fe(2) and Fe(3) structural sites in the 15R form. The magnetic ordering temperatures were determined as 597 ± 3 K for 6H-BaFeO2 F and 636 ± 3 K for 15R-BaFeO2 F. These values are surprisingly close to the value of 645 ± 5 K determined for the cubic form. The magnetic interactions in the three forms are compared with a view to explaining this similarity of magnetic ordering temperature.